Antioxidant and anti-inflammatory activities of methanol and aqueous extracts of Sargassum wightii - Sradhasini Rout; Bandana Rath; Subrat Kumar Bhattamisra; Ishani Rath; Anjan Kumar (Shahrekord University of Medical Sciences, 2022)
Introduction: Antioxidants of natural sources for the treatment of many ailments have taken priority since the last decades. Recently, researches have been focused on marine algae as they are the largest reservoir of bioactive compounds. Hence, the objective of this study was to explore the in-vitro antioxidant and anti-inflammatory activities of methanolic and aqueous extracts of Sargassum wightii. Methods: The total phenolics, flavonoids, and ascorbic acid (AA) contents were evaluated informs of gallic acid equivalent (GAE), rutin equivalent (RUE), and AA equivalent, respectively. The aqueous and methanolic extracts were isolated. The antioxidant activities were explored using2,2-diphenyl-1-picrylhydrazil (DPPH), superoxide dismutase (SOD), hydroxyl radical scavenging, and ferric reducing power assays. The in vitro anti-inflammatory activity was assayed using nitric oxide radical scavenging, inhibition of protein denaturation, and antiproteinase activities. Results: We observed significant changes in DPPH scavenging activity with both methanolicSargassum extract (MSE) and aqueous Sargassum extract (ASE) [IC50: 511.15 µg/mL and 927.05µg/mL, respectively]. Methanolic extract showed a greater SOD scavenging activity [IC50: 369.56µg/mL] and hydroxyl radical scavenging potential [IC50: 668.93 µg/mL] than that of ASE [SOD,IC50: 923.94 µg/mL; hydroxyl ion, IC50: 953.57 µg/mL]. In the Ferric reducing antioxidant power assay, MSE and ASE exhibited absorbance of 0.93±0.12 and 0.59±0.08, respectively, at 1200 µg/mL each. Both methanol and ASEs showed NO- scavenging activity having IC50 in order, AA(96.46 µg/mL) <MSE (963.50 µg/mL) <ASE (1974.88 µg/mL). However, the protein denaturation inhibition and antiproteinase activity of both these extracts at 1000 µg/mL were similar. Conclusion: Sargassum wightii has promising antioxidant and anti-inflammatory activities and could be a potential candidate for drug development targeting oxidative stress-mediated inflammatory diseases.